2012
DOI: 10.1136/gutjnl-2012-302514b.17
|View full text |Cite
|
Sign up to set email alerts
|

PMO-017 Perinatal hepatitis B in a high prevalence inner city population: direct electronic referral improves care

Abstract: symptoms. A similar cohort was identified with age & sex matched controls with FC values <50 mg/g. All the patients who did not go on to have a complete colonoscopy were removed from further analysis. Patients' records were analysed electronically using the NHS Great Glasgow & Clyde Clinical Portal. Results 216 patients were identified with a FC of 50e100 mg/g. After exclusion criteria, 158 patients remained. Of these 82 underwent complete colonoscopy (mean age 36.7, M:F 1:2.2) which was abnormal in only six c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Only two studies 68,69 reported an outcome related to HBV linkage to care. One 69 assessed the eff ect of a letter about local HBV services, and one 68 compared referral rates before and after institution of an electronic patient referral system (appendix).…”
Section: Hbv Linkage To Carementioning
confidence: 99%
“…Only two studies 68,69 reported an outcome related to HBV linkage to care. One 69 assessed the eff ect of a letter about local HBV services, and one 68 compared referral rates before and after institution of an electronic patient referral system (appendix).…”
Section: Hbv Linkage To Carementioning
confidence: 99%
“…13 Another study found that a seamless, direct electronic referral to hepatology for patients diagnosed with HBV during pregnancy-a point of universal screening in the US-significantly increased and accelerated linkage to care and treatment. 14 Likewise, the higher rates of follow-up observed under specialist care suggest that provider familiarity with monitoring and treatment guidelines is an important factor in ensuring that patients receive appropriate care. Chronic HBV is a complex and variable disease;…”
Section: Discussionmentioning
confidence: 99%
“…Rates of specialist referral increased from 28% to 78% after the implementation of this simple intervention 13 . Another study found that a seamless, direct electronic referral to hepatology for patients diagnosed with HBV during pregnancy—a point of universal screening in the US—significantly increased and accelerated linkage to care and treatment 14 …”
Section: Discussionmentioning
confidence: 99%